Image-based visual servoing improvement through utilization of adaptive control gain and pseudo-inverse of the weighted mean of the Jacobians. (May 2020) - Taherian, A.; Mazinan, A.H.; Aliyari-Shoorehdeli, M.
Highlights: Image-based visual servoing is improved through utilizing the proposed controller. Convergence domain of the servoing system is significantly widened. Convergence rate of the servoing system is considerably increased. 3D camera trajectories are improved. High convergence rates are achieved without spending too much excess energy. Abstract: The use of information acquired by stationary or onboard vision sensors for feedback control of pose and motion of a robot is known as visual servoing. In this paper, an image-based visual servoing controller with improved rate and domain of convergence is presented using adaptive control gain and pseudo-inverse of the weighted mean of the Jacobians. Furthermore, the stability of the proposed controller is proved by means of Lyapunov criteria, and simulations results are provided to demonstrate the validity and advantages of this control scheme. In comparison with the pseudo-inverse of the mean of the Jacobians scheme, the proposed controller increased the convergence rate of the servoing system up to seven times when used in complex motion tasks, and widened the convergence domain of the system up to 179° initial camera yaw angle when used in pure rotation tasks.